Should kissing balloon inflation after main vessel stenting be routine in the one-stent approach? A systematic review and meta-analysis of randomized trials. - Ming Zhong; Biao Tang; Qiang Zhao; Jian Cheng; Qiangsong Jin; Shenwen Fu (PLoS ONE, 2018)
The KBI (kissing balloon inflation) technique is considered the default strategy for the two-stent approach in real world practice. Studies comparing KBI and No-KBI in patients undergoing the one-stent approach have reported conflicting results. The meta-analysis was performed to compare the clinical outcomes of the KBI strategy and the No-KBI strategy for coronary bifurcation lesions in the one-stent approach. Five randomized studies were included, and a total of 1264 patients were involved in the meta-analysis. The primary outcome was cardiac death. The secondary end points were stent thrombosis, MI (myocardial infarction), target lesion revascularization (TLR), target vessel revascularization (TVR), and main vessel and side branch restenosis. Compared with the No-KBI strategy, the KBI strategy was associated with a significant reduction in side branch restenosis (OR: 0.44, 95% CI: 0.30-0.64, p<0.001). A high risk of main vessel restenosis was found in the KBI group (OR: 2.96, 95% CI: 1.74-5.01, p<0.001). There were no significant differences in rates of cardiac death (OR: 1.89, 95% CI: 0.60-5.95, p = 0.28), stent thrombosis (OR: 0.98, 95% CI: 0.19-4.94, p = 0.98), MI (OR: 0.68, 95% CI: 0.33-1.44, p = 0.30), TLR (OR 1.14, 95% CI 0.68-1.90, p = 0.62), or TVR (OR 1.27, 95% CI 0.75-2.16, p = 0.38). Compared with the No-KBI strategy, the KBI strategy reduced the incidence of side branch restenosis and increased the risk of main branch restenosis in the one-stent approach. However, the clinical outcomes were similar between the KBI and No-KBI groups.